QUALITY ASSURANCE PELAYANAN GIZI DI PUSKESMAS KOTA BANDUNG - -, Suparman; Ilyas, Nelly Olifa; -, Ichwanuddin (GIZI INDONESIA, 2004)
QUALITY ASSURANCE OF HEALTH CENTER’S NUTITION SERVICES IN BANDUNGA cross-sectional study of quality assurance of nutrition services was conducted in all (68) healthcenters in Bandung. Subjects selected for the study were nutrition staff, maternal and child healthstaff for health provider, pregnant mothers, and mother of under five years old visiting healthcenter for consumer. Nutrition service performance, as the dependent variable, was measured byusing 11 different working activities in nutrition services. Three independent variables associatedwith  performance  were  collected  i.e.  nutrition  education  and  training,  availability  of  workingguidebook and other facilities, and client satisfaction and complain. The study showed that therewas no significant association between nutrition service performance and nutrition education andtraining. A significant association was found between unavailability of working guidebook andservice performance. There was no association between service performance and satisfactionexcept for client compliance. Nutrition services performance varied widely among nutrition serviceproviders.Keywords: quality assurance, nutrition services, health staff